Comparison of Propofol Vs Thiopentone in Post Operative Nausea and Vomiting in Patients Undergoing Laparoscopic Cholecystectomy - Kunwar, Bhuwan Raj; Rijal, Thaneshowr; Thapa, Puja; Rayamajhi, Mallika; Amatya, Biswo Ram (Medical Journal of Shree Birendra Hospital, 2019)
Introduction: Postoperative Nausea and Vomiting (PONV) is one of the commonest causes of significant morbidity in the patients after laparoscopic cholecystectomy. The purpose of this study was to compare the incidence of PONV when propofol and thiopentone were used as induction agents during laparoscopic cholecystectomy. Methods: A prospective, randomised comparative study was conducted in operation theatre at a tertiary level referral hospital of Nepal. A sample size of 100 ASA I - II patients aged between 18 and 70 years were included and scheduled for elective laparoscopic cholecystectomy. The study population were divided into two groups: Group A (Propofol), n = 50 and Group B (Thiopentone), n = 50. These patients were followed up for the first 24 hours postoperatively for any PONV at 0-6 hrs, 6-12 hrs, 12-24 hrs. Results: Out of the 100 patients, PONV was observed almost similar in both groups. i.e. group A (Propofol) n = 31, (62%) and group B (Thiopentone) n = 26 (52%) with no statistical significance (p value = 0.1998) within the first 24 hours postoperatively in both groups; and no significant difference was observed at the different time intervals viz. at 0-6 hrs (p value 0.262): Group A = 45%; Group B = 40%; 6-12 hrs (p value 0.781): Group A = 17.5%, Group B = 22.5%; 12-24 hrs (p value 1.000) Group A = 0%; Group B = 2.5% when using the Fisher exact test. The mean ages for development of PONV in these two groups were: Group A = 40 years and Group B = 38 years. The p-value was 0.5125 which showed no statistical significance. In our study 76% (n = 38) were females and 24% (n = 12) were males in Group A; while 70% (n = 35) were females and 30% (n = 15) males in Group B. However, there was no statistical difference between the two groups in terms of PONV. Conclusions: The study showed that there was a high incidence of PONV during laparoscopic cholecystectomy. However, there was no significant difference in the incidence of PONV when propofol or thiopentone was used.